OPINIOWANIE PRZEZ BIEGŁEGO Z ZAKRESU SLANGU NARKOTYKOWEGO I PRZESTĘPCZOŚCI NARKOTYKOWEJ NA PODSTAWIE MATERIAŁÓW NIEJAWNYCH UZYSKANYCH W WYNIKU PODSŁUCHU TELEFONICZNEGO - Teluk, Rafał (Zeszyty Prawnicze, 2016)
EXPERT OPINIONS CONCERNING DRUG SLANG AND DRUG CRIME COMPILED ON THE BASIS OF TELEPHONE TAPPING DATA Summary This article discusses the value for courts of opinions drawn up by experts on drug slang and drug crime, especially in criminal proceedings involving organised crime. It presents a dictionary of the most frequently used Polish drug slang. The author describes the principles governing the protection of classified information obtained by telephone tapping (lawful interception); he also outlines the limits to the access the expert appointed by the court has to intercepted data on the grounds of their status as classified information. The article addresses the use of the expert’s opinion both in the preliminary proceedings phase as well as in court.